Achieving patient‐centred care: the potential and challenge of the patient‐as‐professional role. (7th July 2014) - Phillips, Rebecca L; Short, Alison; Kenning, Annie; Dugdale, Paul; Nugus, Peter; McGowan, Russell; Greenfield, David
Abstract: Background: The patient‐as‐professional concept acknowledges the expert participation of patients in interprofessional teams, including their contributions to managing and coordinating their care. However, little is known about experiences and perspectives of these teams. Objective: To investigate (i) patients' and carers' experiences of actively engaging in interprofessional care by enacting the patient‐as‐professional role and (ii) clinicians' perspectives of this involvement. Design, setting and participants: A two‐phased qualitative study. In Phase 1, people with chronic disease ( n = 50) and their carers ( n = 5) participated in interviews and focus groups. Phase 2 involved interviews with clinicians ( n = 14). Data were analysed thematically. Findings: Patients and carers described the characteristics of the role (knowing about the condition, questioning clinicians, coordinating care, using a support network, engaging an advocate and being proactive), as well as factors that influence its performance (the patient–clinician partnership, benefits, barriers and applicability). However, both patients and carers, and clinicians cautioned that not all patients might desire this level of involvement. Clinicians were also concerned that not all patients have the required knowledge for this role, and those who do are time‐consuming. When describing the inclusion of the patient‐as‐professional, clinicians highlighted the patient and clinician's roles, the importance of the clinician–patient relationship and ramifications of the role. Conclusion: Support exists for the patient‐as‐professional role. The characteristics and influencing factors identified in this study could guide patient engagement with the interprofessional team and support clinicians to provide patient‐centred care. Recognition of the role has the potential to improve health‐care delivery by promoting patient‐centred care.